Low-Dose Butorphanol Alleviates Remifentanil-Induced Hyperalgesia in Patients Undergoing Laparoscopic Cholecystectomy. Issue 2 (April 2017) - Kong, M.; Yang, L.; Li, J.; Zhong, Z.; Cheng, Y.; Wu, Z.; Guo, R.
Abstract : (Abstracted from J Clin Anesth, 34:41–45, 2016) The objective of this randomized, double-blind clinical trial was to test the hypothesis that low-dose butorphanol can attenuate hyperalgesia induced by high-dose remifentanil infusions in patients undergoing laparoscopic cholecystectomy. Remifentanil, a widely used synthetic opioid, is a potent agonist at the mu-opioid receptor (MOR) and has a short duration of action.